Dampak Implementasi Kebijakan Kenaikan Harga Bahan Bakar Minyak (BBM) Pada Sektor Transportasi - Pohan, Farida Romaito; Al-Farizi, Chairul Wafa (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2023)
The use of fuel oil (BBM) will continue to increase in line with Indonesia's national economic growth. Government decisions to make policies and see their implementation in Indonesia. The concepts of implementation seeems complex and challenging , involving various stages, actors and interactions. The importants points highlighted by Van Meter and Van Horn (in Dwiyanto Indiahono) are Policy Implementation, Actor Interaction, Local Context, Monitoring and Evaluation in the transportation sector at the STIA Karya Dharma Merauke Campus. The aims that achieved in this study was to see the impact of implementing policies made by the government, especially in the transportation sector for STIA Karya Dharma Merauke campus students, especially for students who use their own vehicles or transportation user. This research method is qualitative research. Data collection techniques used are observation, interview, and documentation techniques. The results of this study indicate that the implementation of the policy and the interaction of actors has been running as it should in accordance with the standards and policy targets set by the government. So far, there has been no direct statement from the government to help students deal with the rising price of fuel oil (BBM), so that it hope this problem can immediately become material for consideration by the government to find alternative solutions by maximizing the potential of human resources owned by the Institute. In local contexts that are interrelated where politics greatly influences the situation of the social environment in society and the economy is fundamental in social terms within the community itself, Monitoring and Evaluation that must owened by the policy implementing agency, including, Democratic, responsive, transparent, honest , and able to provide solutions to each problem.